Associations between CAG repeat size, brain and spinal cord volume loss, and motor symptoms in spinocerebellar ataxia type 3: a cohort study - Zhi-Xian Ye; Xuan-Yu Chen; Meng-Cheng Li; Xin-Yuan Chen; Yu-Sen Qiu; Ru-Ying Yuan; Zhi-Li Chen; Min-Ting Lin; Jian-Ping Hu; Ying Fu; Wan-Jin Chen; Ning Wang; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Spinocerebellar ataxia type 3 (SCA3) is a hereditary disease caused by abnormally expanded CAG repeats in the ATXN3 gene. The study aimed to identify potential biomarkers for assessing therapeutic efficacy by investigating the associations between expanded CAG repeat size, brain and spinal cord volume loss, and motor functions in patients with SCA3. Methods In this prospective, cross-observational study, we analyzed 3D T1-weighted MRIs from 92 patients with SCA3 and 42 healthy controls using voxel-based morphometry and region of interest approaches. Associations between expanded CAG repeat size, brain and spinal cord volume loss, and International Cooperative Ataxia Rating Scale (ICARS) scores were investigated using partial correlation and mediation analyses. Sample sizes of potential biomarkers were calculated. Results Compared with healthy controls, SCA3 patients had lower cerebellar volume and cervical spinal cord area. SCA3 patients evolved along a stage-independent decline that began in the cerebellum, progressed to spinal cord, brainstem, thalami, and basal ganglia, and extensive subcortex. Expanded CAG repeat size was associated with right cerebellar lobule IV volume (r = − 0.423, P < 0.001) and cervical spinal cord area (r = − 0.405, P < 0.001), and higher ICARS (r = 0.416, P < 0.001). Mediation analysis revealed an indirect effect of expanded CAG repeat size on ICARS through spinal cord. Sample sizes estimation revealed that a minimum sample size was achieved with spinal cord measures. Conclusions Our results indicate the potential of cervical spinal cord area as a biomarker for disease progression and a minimum sample size estimation in future clinical studies of SCA3.